The origins of transparent and non-transparent white pumice: A case study of the 52 ka Maninjau caldera-forming eruption, Indonesia - Suhendro, Indranova (Elsevier B.V., 2022)
The VEI 7 (220–250 km3), a 52 ka eruption of the Maninjau caldera in Indonesia produced two distinct types of white pumices: transparent (TWP) and non-transparent (NTWP). These pumices were identified on outcrops, based on their qualitative traits, without the use of laboratory analyses (geochemical and textural). TWPs are typically fragile, irregular in shape, and have a transparent glass of vesicle walls around visible large vesicles, whereas NTWPs are relatively strong, blocky in shape, and have a non-transparent glass due to invisible small vesicles. Based on chemical and petrographical analyses, both pumice types were crystal-poor (avg. of 3.3), with similar mineralogy, glass compositions (avg. 78.5 wt SiO2), and plagioclase core compositions (avg. of An28). From component analysis, we found that the abundance of TWP decreased towards the upper stratigraphic ignimbrite deposits, along with an increase in NTWP, grey pumice, banded pumice, and lithic (non-juvenile) contents. We defined two vesicle populations with a threshold diameter of 0.1 mm based on bimodal vesicle size distributions by textural analysis for TWP and NTWP. Large vesicles correspond to preexisting bubbles that form in the magma chamber (pheno-vesicle, > 0.1 mm), whereas small vesicles in the groundmass (matrix-vesicle, < 0.1 mm) are attributed to second nucleation in the conduit during the eruption. We performed a comparison using vesicle data (pheno- and matrix-vesicles) for these two white pumice types. Pheno- and matrix-vesicularity showed a negative correlation. Thus, the boundary between TWP and NTWP was also quantitatively confirmed by the volume fraction ratio of the pheno- and matrix-vesicles. This evidence suggests that TWP originated from pheno-bubble-dominated magma (at least 0.1 volume fraction of pheno-bubbles in the magma chambers), whereas NTWP originated from pheno-bubble-poor magma. The variation in the abundance of TWP and NTWP in the stratigraphic positions implies the rough stratification of pre-existing bubbles (pheno-bubbles) in the pre-eruptive magma chamber, where the overpressure developed to trigger and drive the eruption. The two regimes control the formation of matrix-vesicles: (1) a pheno-bubble-controlled regime, and (2) a decompression-controlled regime. Based on a correlation between pheno-vesicle number density (PVND) and matrix-vesicle number density (MVND) together with numerical calculations based on a previous study, we suggest that the TWPs with the highest pheno-vesicularity formed under conditions corresponding to the first regimes, while the NTWPs formed in the second regime, where MVND is mostly determined by decompression rate. We also argue that NTWP is the only representative juvenile for estimating magma decompression rate, as the MVND value in TWP do not represent the actual second nucleation processes. Therefore, the occurrence of NTWP in the entire deposits with a relatively similar MVNDs value might suggest that the early and final eruption stages experienced a relatively similar magma decompression rate. © 2022 The Authors